Surface-modified PVDF membranes for separation of dye by forward osmosis - Muratow, Marta; Yalcinkaya, Fatma; Bryjak, Marek; Siekierka, Anna (Frontiers in Membrane Science and Technology, 2024)
In this study, the modification of PVDF nanofiber mat by polyamide layers were systematically evaluated to improve separation ability of thin-film composite membranes for dye concentration by means of forward osmosis process. The PA active layer was prepared by a reaction of two cyclic aromatic amines, m-phenylenediamine, or piperazine, and trimesoylchloride. The modification progress was monitored by FTIR analysis, water uptake, nitrogen content, and grafting yields. Investigated membranes show an excellent dye separation features with water flux and dye fluxes strongly related to type of applied amines and reaction time. The best obtained membrane demonstrated outstanding performance in forward osmosis; their water flux was 3.3 LMH and rejection rate of 97% for bromocresol green dye. The membrane allowed increase of dye concentration by 50% after 24 hours of the process.